Estimates of past and future time trends in age-specific breast cancer incidence among women in Karachi, Pakistan: 2004-2025 - Sidra Zaheer; Nadia Shah; Syed Amir Maqbool; Noor Muhammad Soomro (BMC, 2019)
Abstract Background The current demographic trends indicate that breast cancer will pose an even greater public health concern in future for Pakistan. Details on the incidence, disease severity and mortality in respect of breast cancer are limited and without such data, therefore, future health policies or systems in respect of this disease cannot be strategically planned or implemented. The aim of this study was to examine past trends of age-specific breast cancer incidence rates (2004-2015), and to estimate the future volume of breast cancer cases in Karachi through the year 2025. Methods Two statistical methods, namely the functional time series models and the log-linear regression model were used; additionally, their real forecasting efficacy in epidemic time series was also evaluated. Results In the past, women aged 60-64 years had the highest overall breast cancer incidence rates, while from 2016 to 2025, large increases in breast cancer rates among women aged 50 to 64 years are expected. The total projected breast cancer incidence will increase by approximately 23.1% in 2020 to 60.7% in 2025. Cases of breast cancer diagnosed in younger women, aged 30-34 years, will increase from 70.7 to 130.6% in 2020 and 2025 relative to 2015. Conclusions The breast cancer incidence appeared to have been rising more rapidly among post-menopausal women (aged 55 to 59), while a stable increase in incidence in the youngest age group (15-29 years) of women is expected. The results also infer an expected increase in incidence cases of breast cancer among middle aged women in Karachi, Pakistan. An increase in the number of incident cases of cancer has implications for understanding the health-care needs of growing population and the subsequent demands on health-care system.